Analisis Perlindungan Hukum Terhadap Pekerja Putting Out System di Jawa Timur - Niken Nendy Istaqnaligh Sanda; Ulfa Arinta; Sholahuddin Al-Fatih (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
The issue of homeworkers is still in the spotlight about a lack of guarantees of the health, safety and rights they should get.  This study is determined to find out how the legal protection of home workers by putting out the system.  Homeworkers who work as a put out system whose existence is not protected by the law.  The government must be present to protect homework that is very susceptible. Keywords: Putting Out System, Homeworkers